Gambaran Pengembangan Kepercayaan Diri pada Peserta Didik Berkebutuhan Khusus (PDBK) di SMA “X” Kabupaten Gresik - Ayu Rinata; Muhimmatul Hasanah; Prianggi Amelasasih (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Not all humans have self confidence. Something that can make someone has less confidence is their disability. The aim of this research is to know an overview of the special needs students’ self confidence development in SMA “X” Gresik Regency. This research used qualitative research method, with subjects: student with autism, slow learner, and light mentally disabled. Data collectives method that used are observation, interview, and documentation. Analysis data method used Miles and Huberman Model. This research used triangulation of technique and sources for checking data credibility. This research shows that student with autism can do activities by himself, believe with what he does, responsible, realized and accepted his imperfection, knows reason and effect behind his action, can build interaction with others, adaptation with environment, and tolerance with others. Student with slow learner can do activities and make decision by himself, responsible, realized and accepted his imperfection, knows reason and effect behind his action, adaptation with environment, and tolerance with others. In the other hand, students with light mentally disabled can not approach directly, need more time to approach them. The closest person have important role for special needs students’ self confidence development, like family, special needs teachers, and classmates.